Preventing, reducing, and attenuating restraint: A prospective controlled trial of the implementation of peer support in acute psychiatry - Badouin, Julia; Bechdolf, Andreas; Bermpohl, Felix; Baumgardt, Johanna; Weinmann, Stefan (Frontiers in Psychiatry, 2023)
Introduction: The use of restraint as a means of managing patients is considered a critical factor that interferes with recovery. Strategies to create a less restrictive environment within psychiatric facilities are therefore eagerly sought. Peer support workers (PSWs) are increasingly employed in mental health settings. The prevailing theory is that PSWs have the potential to contribute to conflict and restraint prevention efforts in acute psychiatric wards. However, to date, research in support of this claim remains limited. Objective: The present study aimed at assessing the effectiveness of employing peer support workers with regard to reducing the use of restraint. Methods: This prospective controlled pre–post study sought to evaluate the implementation of peer support in one locked ward compared to treatment as usual (TAU) with no implementation of peer support in a second locked ward of a psychiatry department in Berlin, Germany. The pre–post comparison was planned to consist of two assessment periods of three months each, taking place directly before and after peer support implementation or TAU. Both assessments were extended to a period of six months, before and after the 12-month implementation process, in order to balance the effects of disruptions and of the COVID-19 pandemic. Using routine data, the proportion, frequency, and duration of mechanical restraint, forced medication as well as mechanical restraint in combination with forced medication, were evaluated. Results: In the control group, an increase in the proportion of patients subjected to measures of restraint was found between pre– and post–assessement, which was accompanied by a further increase in the mean number of events of restraint per patient within this group. In the intervention group, no significant change in the application of restraint was observed during the study period. Discussion: There is some indication that peer support may be protective with regard to restraint in acute wards. However, our study faced major challenges during the implementation process and the post–assessment period, such as COVID-19 and staff reorganization. This may have led to peer support not reaching its full potential. The relationship between the implementation of peer support and the use of restraint therefore merits further investigation.